On the Friction and Lubrication of 3D Printed Ti6Al4V Hip Joint Replacement - Rebenda, David; Odehnal, Lukáš; Uhrová, Simona; Nečas, David; Vrbka, Martin (Springer Nature, 2025)
The present study investigates the tribological performance of 3D printed Ti6Al4V total hip replacements (THR) compared to conventionally produced THRs from CoCrMo and FeNiCr alloys. The objective was to evaluate the suitability of 3D printed titanium alloy, with and without DLC coating, for THR rubbing surfaces and to investigate the potential benefits of 3D printing technology for friction and lubrication. A pendulum hip joint simulator was employed to replicate the swinging motion of a hip joint, thereby enabling the measurements of coefficient of friction (COF) and the observation of lubricant film formation under realistic conditions between the metal femoral head and acetabular cup. The experiments demonstrated that additive manufacturing enables the creation of specific surface topographies that can enhance protein adsorption, but also introduce surface imperfections negatively affecting tribological properties. The elevated surface roughness of additively manufactured femoral heads did not inevitably result in an increase in COF and was comparable to that of conventionally manufactured femoral heads. The additively manufactured Ti6Al4V head without DLC coating also exhibited a more rapid increase in lubricant film thickness during dynamic motion. In conclusion, the findings indicate that while 3D printing offers promising advancements in implant customization and material properties, its application requires careful consideration of surface finishing and coating methods to achieve optimal tribological performance.

The present study investigates the tribological performance of 3D printed Ti6Al4V total hip replacements (THR) compared to conventionally produced THRs from CoCrMo and FeNiCr alloys. The objective was to evaluate the suitability of 3D printed titanium alloy, with and without DLC coating, for THR rubbing surfaces and to investigate the potential benefits of 3D printing technology for friction and lubrication. A pendulum hip joint simulator was employed to replicate the swinging motion of a hip joint, thereby enabling the measurements of coefficient of friction (COF) and the observation of lubricant film formation under realistic conditions between the metal femoral head and acetabular cup. The experiments demonstrated that additive manufacturing enables the creation of specific surface topographies that can enhance protein adsorption, but also introduce surface imperfections negatively affecting tribological properties. The elevated surface roughness of additively manufactured femoral heads did not inevitably result in an increase in COF and was comparable to that of conventionally manufactured femoral heads. The additively manufactured Ti6Al4V head without DLC coating also exhibited a more rapid increase in lubricant film thickness during dynamic motion. In conclusion, the findings indicate that while 3D printing offers promising advancements in implant customization and material properties, its application requires careful consideration of surface finishing and coating methods to achieve optimal tribological performance.
On the Friction and Lubrication of 3D Printed Ti6Al4V Hip Joint Replacement
Keywords: Total hip replacement; Ti6Al4V; DLC coating; Lubricant film formation; Friction; Total hip replacement; Ti6Al4V; DLC coating; Lubricant film formation; Friction